Graphene oxide polymer film as q-switcher and mode-locker in 1.5 micron region /Fauziah Che Mat - Fauziah, Che Mat (2018)
This project aimed to demonstrate passively Q-switched and Mode-locked Erbium-Doped Fiber Laser (EDFL) that operated in 1.5 micron region using Graphene Oxide (GO) as saturable absorber (SA) for possible applications in telecommunication, laser processing, fiber sensing and medical. A passively Q-switched EDFL was successfully demonstrated using the GO based SA. The Q-switched laser operates at wavelength between 1550nm to 1580nm with a repetition rate that can be tuned from 44.33 kHz to 61.77 kHz as the pump power is varied from 130mW to 260mW. The highest repetition rate of 61.77 kHz is achieved at a pump power of 260mW and it is observed that the Q-switched pulse produced maximum pulse energy of 0.054nJ. Nanosecond mode-locked fiber laser in three different EDFL cavities was also successfully demonstrated using GO based SA. The mode-locking threshold pump powers are 65.5, 65.5 and 60.2mW for the EDFL configured with SMF lengths of 50, 100 and 200m, respectively. The stable mode-locking operation could be sustained up to the pump power of 80.4mW for all three lasers. With 208m cavity length and total dispersion of -4.77ps2, the EDFL operates at 1566nm with repetition rate of 0.9625MHz, pulse width of 380 ns, peak power of 16.29mW, pulse energy of 7.06nJ when the pump power was fixed at 80.4mW. The repetition rates increased from 0.9625 to 3.266MHz with the reduction of cavity length from 208 to 50m. These results indicate that GO film have a great potential for pulse generation at 1.5μm.